Antidiabetic potential of Lavandula stoechas aqueous extract: insights into pancreatic lipase inhibition, antioxidant activity, antiglycation at multiple stages and anti-inflammatory effects - Elrherabi, Amal; Abdnim, Rhizlan; Loukili, El Hassania; Laftouhi, Abdelouahid; Lafdil, Fatima Zahra; Bouhrim, Mohamed; Mothana, Ramzi A.; Noman, Omar M.; Eto, Bruno; Ziyyat, Abderrahim; Mekhfi, Hassane; Legssyer, Abdelkhaleq; et al. (Frontiers in Pharmacology, 2024)
Background: With the increasing global prevalence of type 2 diabetes (T2D) and obesity, there is a pressing need for novel therapeutic interventions. Lavandula stoechas, a medicinal plant traditionally used for various ailments, holds promise as a potential agent for T2D management, particularly in Morocco, where it is commonly used to treat diabetes. This study aims to evaluate the pharmacological potential of Lavandula stoechas aqueous extract (AqLs) by assessing its lipase inhibition antioxidant and anti-inflammatory activities, identifying phenolic compounds, and examining its efficacy in reducing diabetic complications.The pharmacological potential of Lavandula stoechas aqueous extract was investigated using in vitro assays. The inhibitory effect on pancreatic lipase, antioxidant power (FRAP), and antiinflammatory activity (albumin denaturation method) was assessed. High-performance liquid chromatography (HPLC) analysis identified phenolic compounds. Additionally, albumin glycation was evaluated by estimating fructosamine, carbonyl groups, and amyloid β-structures to assess efficacy in mitigating diabetic complications.The extract demonstrated concentration-dependent inhibition of pancreatic lipase (IC50 = 0.132 ± 0.006 mg/mL), potent antioxidant activity (IC50 = 604.99 ± 1.01 µg/mL), and dose-dependent anti-inflammatory effects (IC50 = 207.01 ± 34.94 mg/mL). HPLC analysis revealed phenolic compounds: naringin (38.28%), syringic acid (25.72%), and cinnamic acid (15.88%) were the most abundant, with 4-hydroxybenzoic acid, hydrated catechin, and catechin ranging from 9.60% to 5.24%, and p-coumaric acid (1.73%). Furthermore, the extract inhibited albumin glycation and fructosamine production, suggesting efficacy in mitigating diabetic complications.These findings highlight the multifaceted pharmacological potential of Lavandula stoechas aqueous extract in T2D management, suggesting that this plant can be highly beneficial for diabetic individuals.